Database GIS delle strade Un sistema di calcolo percorso ciclabile nel Comune di Roma - Ieradi, Michele; Perla, Annalisa; Surgo, Davide (GEOmedia, 2008)
A GIS database for roads and bicycle paths: a cycle route processing system in Rome municipality ATAC, the mobility Agency of Rome municipality, incorporates GIS methodologies for the management of territorial data. ATAC will present the procedure followed to realise a best routing calculation system for cyclists, designed from the existing system developed for PT users in Rome, available on ATAC web site (www.atac.roma.it). Thanks to this project ATAC has created a network of cycling pathways, created by mashing up the following information: the road network, bicycle paths, street slopes and other information derived from the Mobility Centre. The service developed will allow the Roman citizens to find out the best route from one point to another in the Capital that can be reached either by bicycle, public transport or a combination therof.